Gambaran makroskopik dan mikroskopik pankreas pada hewan coba postmortem - Goni, Livya R.; Wongkar, Djon; Ticoalu, Shane H.R. (Universitas Sam Ratulangi, 2017)
Abstract: Medicolegal examination is beneficial in police investigation inter alia to determine the time of death and causes as well as mechanisms of death. Postmortem macroscopic and microscopic changes could be alternatives to estimate the time of death. This study was aimed to obtain the microscopic and macroscopic postmortem changes in pancreas based on the variation of time up to 48 hours. This was a descriptive observational study using two domestic pigs as animal model. Pancreas samples were obtained at time intervals as follows: 0 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 33 hours, 36 hours, 39 hours, 42 hours, and 48 hours postmortem. The macroscopic examination showed changes in its consistency at 8 hours postmortem, followed by changes in color, consistency, and length during 39 hours postmortem. Microscopic changes of pancreas occurred at 2 hours postmortem as congestion of the acini. At 5 hours postmortem, the acinar cells were difficult to be identified; most of their nuclei were distributed out of the cells. At 8 hours postmortem the structures of acini could not be identified and the cells had undergone karyolysis. At 10 hours postmortem the structures of all acini could not be identified. Conclusion: Postmortem macroscopic changes of pancreas began at 8 hours postmortem meanwhile microscopic changes began at 2 hours postmortem as acinar congestion. At 8 hours postmortem most aciniâ€™s structures could not be identified and their cellsâ€™ nuclei underwent karyolysis.Keywords: macroscopic and microscopic changes, postmortem, pancreasÂ Abstrak: Pemeriksaan medikolegal sangat bermanfaat bagi bidang pnyidikan untuk menentukan lama kematian, penyebab kematian, serta mekanisme kematian suatu individu. Perubahan makroskopik dan mikroskopik postmortem dari organ tubuh dapat dijadikan sebagai alternatif untuk memperkiraan waktu kematian. Penelitian ini bertujuan untuk mendapatkan gambaran makroskopik dan mikroskopik organ pankreas postmortem berdasarkan variasi waktu sampai 48 jam. Jenis penelitian ialah deskriptif observasional dengan menggunakan dua ekor babi domestik sebagai hewan coba. Sampel pankreas diambil pada interval waktu 0 jam, 1 jam, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 8 jam, 10 jam, 12 jam, 14 jam, 16 jam, 18 jam, 20 jam, 22 jam, 24 jam, 26 jam, 27 jam, 30 jam, 33 jam, 36 jam, 39 jam, 42 jam, 45 jam, dan 48 jam postmortem. Hasil penelitian menunjukkan perubahan makroskopik pankreas pada hewan coba dimulai pada 8 jam postmortem berupa perubahan konsistensi, diikuti perubahan warna, konsistensi, dan panjang pankreas pada 39 jam postmortem. Perubahan mikroskopik pankreas dimulai pada 2 jam postmortem berupa kongesti asini pankreas. Pada 5 jam postmortem sel-sel asini telah sulit diidentifikasi; sebagian besar inti sel sudah tersebar di luar sel. Pada 8 jam postmortem struktur sebagian besar asini sudah tidak jelas dengan sel-sel yang mengalami kariolisis. Pada 10 jam postmortem struktur seluruh asini pankreas tidak dapat diidentifikasi. Simpulan: Perubahan makroskopik pankreas dimulai pada 8 jam postmortem. Perubahan mikroskopik dimulai pada 2 jam postmortem berupa kongesti asini; dan sejak 8 jam postmortem struktur asini sudah tidak jelas dengan sel-sel yang mengalami kariolisis. Kata kunci: perubahan makroskopik dan mikroskopik, postmortem, pankreas